Peran Pengadilan Tata Usaha Negara dalam Menyelesaikan Sengketa Pertanahan: Studi Kasus Putusan 13/G/2024/PTUN.JBI - Bisma Bintang Pradipta (Uniku Law Review, 2025)
This study analyzes the role of the State Administrative Court (PTUN) in resolving land disputes. The purpose of this study is to determine the regulation of the State Administrative Court in resolving land disputes and the application of the State Administrative Court in resolving land disputes in Decision 13/G/2024/PTUN.JBI. The method used in this paper is normative juridical. The results of the study show that the regulation and application of the authority of the State Administrative Court (PTUN) in resolving land disputes are the result of important developments in the administrative law system in Indonesia. The underlying laws, such as the PTUN Law, the State Administration Law, PP 24/1997, PERMA 6/2018, Perpres 48/2020, and SEMA 5/2021, and Decision Number 13/G/2024/PTUN.JBI, demonstrate how the Jambi State Administrative Court exercised its judicial function in assessing the validity of the State Administrative Decree (KTUN) regarding the issuance of two land ownership certificates (SHM 1480/Paal Merah and SHM 6863/Paal Merah) that allegedly overlapped with SHM 788/Paal Merah, land belonging to Tarmizi's heirs.